(untitled) (Ameghiniana, 2014)
The Languiñeo-Genoa Basin in Patagonia, displays a continuous sedimentary sequence from Lower Carboniferous to Lower Permian. The study of marine invertebrate assemblages from several fossiliferous levels and localities, allows to confirm a close comparison between sections in separated exposures. Correlation of the upper marine horizons suggests a new interpretation for the stratigraphical position of some sections to the east of rio Genoa. The presence of the Cancrinella fauna at the southern extremity of the Basin, reveals the persistence of the Tepuel Group in a larger area than previously suspected. ·